Hydrogen storage properties of nanoconfined LiBH4-NaBH4 - Javadian, P.; Sheppard, Drew; Buckley, Craig; Jensen, T. (2015)
In this study a eutectic melting composite of 0.62LiBH4-0.38NaBH4 has been infiltrated in two nanoporous resorcinol formaldehyde carbon aerogel scaffolds with similar pore sizes (37 and 38 nm) but different BET surface areas (690 and 2358 m2/g) and pore volumes (1.03 and 2.64 mL/g). This investigation clearly shows decreased temperature of hydrogen desorption, and improved cycling stability during hydrogen release and uptake of bulk 0.62LiBH4-0.38NaBH4 when nanoconfined into carbon nanopores. The hydrogen desorption temperature of bulk 0.62LiBH4-0.38NaBH4 is reduced by ~107 °C with the presence of carbon, although a minor kinetic variation is observed between the two carbon scaffolds. This corresponds to apparent activation energies, EA, of 139 kJ mol-1 (bulk) and 116-118 kJ mol-1 (with carbon aerogel). Bulk 0.62LiBH4-0.38NaBH4 has poor reversibility during continuous hydrogen release and uptake cycling, maintaining 22% H2 capacity after four hydrogen desorptions (1.6 wt.% H2). In contrast, nanoconfinement into the high surface area carbon aerogel scaffold significantly stabilizes the hydrogen storage capacity, maintaining ~70% of the initial capacity after four cycles (4.3 wt.% H2).